2014
DOI: 10.1002/adhm.201400391
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Stimulation of MCF7 Cells with Rod‐Shaped Fe–Au Janus Particles Induces Cell Death Through Paradoxical Hyperactivation of ERK

Abstract: Multifunctional nanoparticles that actively target specific tissues are studied for cancer diagnosis and treatment. Magnetically and optically active particles are of particular interest because they enable multiple imaging modalities and physically modulated therapies, such as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 54 publications
(73 reference statements)
1
56
0
Order By: Relevance
“…[9] Mechanics plays important roles in numerous physiological and pathological processes and is particularly important for cancer, since metastatic cancer accounts for over 90% of cancer-related deaths and forces acting on cells can modulate the metastatic process. [10] Metastasizing cells detach from the primary tumor, migrate through the extracellular matrix, enter the vasculature by squeezing through the endothelial cells, adhere to the endothelial cells, and exit the vasculature once again by penetrating the endothelium to eventually form a secondary tumor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] Mechanics plays important roles in numerous physiological and pathological processes and is particularly important for cancer, since metastatic cancer accounts for over 90% of cancer-related deaths and forces acting on cells can modulate the metastatic process. [10] Metastasizing cells detach from the primary tumor, migrate through the extracellular matrix, enter the vasculature by squeezing through the endothelial cells, adhere to the endothelial cells, and exit the vasculature once again by penetrating the endothelium to eventually form a secondary tumor.…”
Section: Introductionmentioning
confidence: 99%
“…[13] An alternative approach would be to use mechanical stimulation to selectively kill tumors and circulating tumor cells. This could be achieved either through damaging the target cell’s membrane or its intracellular structures, [9c] or through activating select mechanotransduction pathways to induce cell death. [9b] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In the second approach, peptides with randomly mixed amino acid sequences are used to show decreased binding efficiency of nanoparticles. 36 40 The increase in ERK phosphorylation was associated to the existence of "active zones," i.e., dynamic regions in the cell periphery, exhibiting higher rates of nanoparticle binding compared to the rest of the cell, suggesting, therefore, a localized receptor activation.…”
mentioning
confidence: 99%
“…40 The authors showed that nanoparticle size between 40-50 nm is critical to be internalized via receptor- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 15 inside the cells by laser confocal scanning microscopy in scattering (reflective) mode, as reported by Rotello et al 41 Also, larger anisotropic gold nanoparticles can be detected in living cells and followed in their intracellular dynamics. 42 In our study, we applied this technique to investigate the internalization kinetics of NPY-conjugated AuNCs into PC3 cells.…”
mentioning
confidence: 99%